Standardization of CTC AR‐V7 PCR assay and evaluation of its role in castration resistant prostate cancer progression. Issue 1 (23rd August 2018) - Tommasi, Stefania; Pilato, Brunella; Carella, Claudia; Lasorella, Antonia; Danza, Katia; Vallini, Ivan; De Summa, Simona; Naglieri, Emanuele
Abstract : Background: Castration resistant prostate cancer (CRPC) represents the most aggressive status of this neoplastic disease, also characterized by the absence of biomarkers predictive of clinical outcome. New drugs as abiraterone or enzalutamide, affecting androgen receptor pathway at different levels, inhibit the proliferative advantage of prostate cancer cells with important long term benefits. Despite the advantages of this second‐generation androgen deprivation therapy (ADT), resistance mechanisms, primitive or acquired, often develop. The existence of androgen receptor (AR) splice variants (AR‐Vs), in particular AR‐V7 expression detected in circulating tumor cells (CTCs), represents an example of acquired resistance, as evidenced in preclinical and clinical studies. Recent studies also have suggested the role of AR‐V7 as a prognostic biomarker in mCRPC. In this field, hot topics are the methodology used to isolate CTC and the assay for AR‐V7 measurement. Our study aims to develop a standardized operating procedure (SOP) to evaluate AR‐V7 in CRPC. Method: The application of a realized cell based Reference Sample as Standardized Quality Control tool for CTC‐AR‐V7 assay has been shown. Then the development, the performance evaluation and contextualization in a clinical setting of this standardized operating procedure (SOP) have been reported to evaluate the prognostic biomarker AR‐V7 in metastatic prostate cancer. Results and Conclusions: The standardized procedure has high sensitivity and specificity and enables the detection and quantification of the spliced variant with respect to the full length AR (AR‐FL) mRNA in CTC DNA purified from the blood of patients with CRPC. This procedure has been further validated in a consecutive series of patients with mCRPC, confirming its role as prognostic biomarker.